The Ba‘alawi Lineage Dispute: A Foucaultian Perspective on Ḥadīth about Ahl al-Bayt in Social Media Debates - Muhammad Sulaiman Hasyim; Hasan Mahfudh (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2025)
This article analyzes the claims made by the Instagram account @hadits_lemah regarding the controversy over the validity of the Ba‘alawi lineage through Michel Foucault’s theory of power and knowledge. The analysis of ḥadīths related to lineage and Ahl al-Bayt reveals that the content posted by @hadits_lemah, which questions the authenticity of Fāṭimah’s lineage, has sparked significant controversy. The account refers to Shaykh al-Albānī to label the ḥadīth as weak (ḍa‘īf), leading many to conclude that Fāṭimah’s lineage was cut off, although further analysis confirms the ḥadīth’s weakness. The provocative content has triggered harsh responses, including insults and slander directed at Habibs and the Ba‘alawi in Indonesia. What began as a scholarly discourse has devolved into personal attacks and hate speech, driven by dissatisfaction with specific Ba‘alawi figures who are perceived not to be descendants of the Prophet due to their lack of prophetic ethics. In contemporary Indonesian Islam, respect for the Ahl al-Bayt of the Prophet is deeply rooted in the teachings of the Qur’an and ḥadīth, though its practice varies among scholars. While some emphasize respect regardless of character, others argue that respect should be based on piety and righteous deeds, underscoring that actions, not lineage, determine nobility in Islam.